2004
DOI: 10.1007/s00296-004-0485-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of lidocaine injection, botulinum toxin injection, and dry needling to trigger points in myofascial pain syndrome

Abstract: Injection is more practical and rapid, since it causes less disturbance than dry needling and is more cost effective than BTX-A injection, and seems the treatment of choice in MPS. On the other hand, BTX-A could be selectively used in MPS patients resistant to conventional treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
214
1
9

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 289 publications
(231 citation statements)
references
References 31 publications
7
214
1
9
Order By: Relevance
“…Seven BoNT serotypes are known to exist (A-G), all of which are produced by strains of the bacterium Clostridium botulinum. BoNT causes the paralytic syndrome botulism, but also holds therapeutic application in the treatment of dystonias [3][4][5][6], spasticity [7,8], facial rhytides [9], axillary hyperhidrosis [10,11], and some pain syndromes [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Seven BoNT serotypes are known to exist (A-G), all of which are produced by strains of the bacterium Clostridium botulinum. BoNT causes the paralytic syndrome botulism, but also holds therapeutic application in the treatment of dystonias [3][4][5][6], spasticity [7,8], facial rhytides [9], axillary hyperhidrosis [10,11], and some pain syndromes [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…41 A hand search of that review produced 2 articles that met our inclusion criteria that were not previously identified with our electronic search. All other key references, 1,4,9,15,17,[20][21][22][23]26,43 as well as 1 other systematic review 8 on the topic, were hand searched but did not yield any additional articles. One article 39 published online (ahead of print) in November 2012 was added to the review.…”
mentioning
confidence: 99%
“…En un estudio comparativo a simple ciego entre la lidocaína, toxina botulínica y aguja seca para la inactivació n de los PG Kamanli et al, en 29 pacientes con dolor miofascial, demostraron que la infiltració n con lidocaína era má s rá pida, efectiva y causaba menos molestias que la aguja seca, ademá s de tener un mejor coste beneficio que la toxina botulínica 43 . Por otro lado, Langford et al utilizaron una combinació n para infiltraciones de lidocaína, bupivacaína y triancionolona con el fin de tratar PG del mú sculo elevador del ano en 18 mujeres.…”
Section: Infiltraciones Con Anestesia Localunclassified